ANALISIS EFEKTIVITAS PREVENTIVE MAINTENANCE PADA AUTOMATIC NAIL MACHINE DI CV. TIGA BHAKTI - Saiful Bahri; Handy Febri Satoto (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Production machines are a vital part owned by a company engaged in manufacturing production, so the company must optimize the use or operation of production machines. Optimization of the production process is also balanced with maintenance that is carried out periodically so that the machine does not experience fatal damage (Corrective Maintenance) which causes maintenance costs to be greater and also interferes with production process activities so that the target demand is not met, As for the purpose of carrying out maintenance, among others, so that the production namely Automatic Nail Machine runs optimally, the company can increase the amount of production, shortening production time, preventing work accidents caused by machines and the production process can run smoothly, the way it is done is by maximizing maintenance by applying the methods owned and also requires better alternative methods. This study uses the method (Age Raplacement) which aims to determine the cost of maintaining machines that have been and will be carried out maintenance, so that researchers can provide alternatives in optimizing the treatment process that can help companies overcome high maintenance costs. After calculating using the Age Replacement method and using minitab18 software, the results obtained before maintenance costs reached Rp. 16,144,000. and after maintenance using the Age raplacement method obtained a decrease in maintenance costs to Rp11,473,401